Donepezil loaded PLGA Nanoparticles, from Modified Nano-Precipitation, an Advanced Drug Delivery System to treat Alzheimer Disease. Issue 1 (March 2021) - Tripathi, S K; Patel, B; Shukla, S; Pachouri, C; Pathak, S; Pandey, A
Abstract: In present works we synthesized Donepezil loaded PLGA nanoparticles (NPs). The approach of our research group was to prove the improvement of drug transport through the Blood Brain Barrier when donepezil was loaded with PLGA. It promoted the uptake of drug into brain endothelium compared with the free drug and play a significant role in the treatment of Alzheimer's disease (AD). The NPs were synthesized by modified Nano precipitation method. These synthesized polymeric nanoparticles were characterized for particle size, Polydispersity index (PDI) and Zeta potential. The average size and PDI of drug loaded polymeric nanoparticle for preferred formulation were found to be 40.8 nm and 0.188 respectively. The Entrapment Efficiency was 74% and Process yield was 78%. The electron microscopic images of polymeric nanoparticles suggested that the particles were spherical in shape. The pharmacokinetics showed that the release behavior of NPs were very much similar to sustained release and follow Hixson Crowell model.